PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS KOLEGIAL PADA PROFESIONALITAS DOSEN DISEKOLAH TINGGI AGAMA ISLAM NEGERI GAJAH PUTIH TAKENGON, ACEH TENGAH ACEH - Saifullah Saifullah (JP : JURNAL PENDIDIKAN, 2019)
Abstract: The Collegial-Based Learning Model is an interesting concern because it is one of the learning components included in the education system in tertiary institutions. The roles, duties and responsibilities of lecturers are very meaningful to produce quality resources. The Collegial-Based Learning Model should be supported by the professionalism of lecturers. However, professionalism of lecturers is not always directly proportional to the existing reality. Many are pointed out that lecturers do not yet have professional abilities. The professional quality of lecturers is still low and not yet maximal even in the lecturer class as the main actor so students are dominantly passive. This study aims to develop a Collegial-Based Learning Model in enhancing the professionalism of lecturers in the Islamic High School of the State of Gajah Putih, Takengon, Central Aceh, Aceh. This study uses an R&D approach and the methodology of naturalistic phenomenology. The instrument used in this study was a questionnaire which included interview and obser-vation guidelines. The questionnaire was used to collect data on responses, two experts, waka I, LPM Chairperson, one person study program chair, two lecturers, and 36 students. While interviews are used to find the opinions of experts, those chosen to provide additional informationKeywords: Learning Model, Collegial, Professionalism